CASES OF BREACHING MINIMUM PENAL LIMITS DUE TO DISPROPORTIONALITY WITH CULPABILITY AND HARMFULNESS - Serrano, Manuel (2025)
One of the most widespread legislative strategies in the criminal field involves establishing minimum and maximum limits for each offense. In this way, when determining the sentence for a specific case, judges use these limits as guides for the level of censure to be applied to the committed conduct. Among the elements judges rely upon for this determination are the culpability of the agent at the time of committing the act and the harmfulness of their criminal behavior. However, there are certain cases in which the minimum penalty appears disproportionate to the censure deserved by the agent. In particular, this paper will address these situations to reconstruct some existing legal and political philosophy discussions.